Effect of examination stress on blood sugar in medical students - Sunil Kumar Jena; Akshaya Kumar Misra; Arati Mohanty (Wolters Kluwer Medknow Publications, 2016)
Background: It has been proved by different research works that examination is a stress factor for students. Medical curriculum is as such stressful for students. Thus, in this study, researchers proposed to observe the changes in blood sugar level owing to examination stress in medical students. Materials and Methods: A general questionnaire was distributed among 1st year MBBS students for selection of subjects. The questionnaire included demographic data, history of diseases, history of drug abuse, and family history of diseases. After the return of questionnaires, 49 1st year MBBS students were selected for this study. Baseline data of heart rate (HR), blood pressure (BP), and fasting blood sugar (FBS) were observed 1 month before beginning of the first professional examination. Then, the second setting of the same data as baseline was observed on the day of practical and viva examination. Data analysis was done by paired t-test to find out the effect of examination on different parameters. P< 0.05 was considered to be significant. Results: Examination stress was responsible to raise HR, systolic and diastolic BP, and FBS from baseline significantly at P< 0.001. Conclusion: As shown in results, the effect of examination raises HR and BP from baseline, confirming that examination creates some stress on students. Thus, it was assumed that examination stress is responsible to raise blood sugar level that is essential to supply extra energy to vital organs.